2011
DOI: 10.1007/s11999-010-1483-5
|View full text |Cite
|
Sign up to set email alerts
|

Total Ankle Arthroplasty in Patients with Hereditary Hemochromatosis

Abstract: Background More than half of patients with hereditary hemochromatosis (HH) have painful arthritis, often including hindfoot osteoarthritis. Total ankle arthroplasty (TAA) is increasingly recommended for patients with painful ankle osteoarthritis. However, the pain relief and function experienced by patients continues to be debated particularly as compared with ankle fusion. Questions/purposes We asked whether (1) the complication rates were low; (2) the components were stable; (3) the patients achieved pain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Revision surgery occurred 1021 times and was reported in 82.9% of papers (97/117). Of the 20 studies that did not report revisions, 6 were designed to analyze specific outcomes, 6,14,50,56,63,66 4 had an average follow-up shorter than 2 years, 7,45,61,62 and 3 studied fewer than 20 arthroplasties. 5,25,35…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Revision surgery occurred 1021 times and was reported in 82.9% of papers (97/117). Of the 20 studies that did not report revisions, 6 were designed to analyze specific outcomes, 6,14,50,56,63,66 4 had an average follow-up shorter than 2 years, 7,45,61,62 and 3 studied fewer than 20 arthroplasties. 5,25,35…”
Section: Resultsmentioning
confidence: 99%
“…Revision surgery occurred 1021 times and was reported in 82.9% of papers (97/117). Of the 20 studies that did not report revisions, 6 were designed to analyze specific outcomes, 6,14,50,56,63,66…”
Section: Occurrence Reporting Of Adverse Eventsmentioning
confidence: 99%
“…Heterotopic ossification is fairly common after total hip and knee replacement, 16,17 with a reported incidence ranging between 2% and 90% but severe functional loss only affects between 1% and 2% of patients. 18 The incidence of ossification after TAR also varies greatly between 7% and 64%, 6,10,[19][20][21][22][23] but the literature contains little information about its natural history and clinical significance. Some reports have suggested it as a source of pain.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of arthrofibrosis in our small series seemed comparable to that previously recognized with primary TAR. Other studies suggest that arthrofibrosis occurs in up to 22% of patients undergoing primary TAR [5,6,14,31,32]. Hintermann et al [27] reported clinical and radiographic outcomes in 28 patients who underwent 30 conversion procedures.…”
Section: Discussionmentioning
confidence: 99%